Pharmacokinetics and absorption mechanism of tandospirone citrate - Li, Rong; Chen, Yuwen; Jia, Mi; Jiang, Xuehua; Wang, Ling (Frontiers in Pharmacology, 2023)
Tandospirone citrate (TDS) is commonly used for the treatment of generalized anxiety disorder in clinical practice, and several studies are developing new indications for TDS. However, the in vivo processes and absorption properties of TDS have not been systematically investigated.This work, we conducted a comprehensive investigation using in vivo, in vitro, and ex vivo approaches, involving animal and cellular models, to examine the pharmacokinetic properties and absorption mechanisms of TDS. The results of in vivo studies revealed that the half-life (t 1/2 ) of TDS was 1.380 ± 0.46 h and 1.224 ± 0.39 h following intragastric (i.g.) and intravenous (i.v.) administration of 20 mg/kg TDS, respectively. This indicates that TDS is rapidly eliminated in rats.The area under the curve (AUC) of TDS after i.g. and i.v. administration was 114.7 ± 40 ng/mL*h and 48400 ± 19110 ng/mL*h, respectively, and the absolute bioavailability of TDS was found to be low (0.24%). Furthermore, TDS was extensively metabolized in rats, with the AUC of the major active metabolite (1-[2-pyrimidyl]-piperazine) being approximately 16.38-fold higher than that of TDS after i.g. administration. The results from the in vitro Caco-2 cell model and ex vivo everted gut sac experiment demonstrated that TDS exhibited good permeability, and its transport was influenced by concentration, temperature and pH. Passive diffusion was identified as the main absorption mechanism. In conclusion, TDS is classified as a Biopharmaceutics Classification System (BCS) class I drug, characterized by high solubility and permeability. The low absolute bioavailability of TDS may be attributed to its rapid metabolism. The pharmacokinetic data and absorption characteristics obtained in this study provide fundamental information for the further development and utilization of TDS.